2006
DOI: 10.1021/bi061275f
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Cation−π Interactions to Protein Stability

Abstract: Calculations predict that cation- interactions make an important contribution to protein stability. While there have been some attempts to experimentally measure strengths of cation-pi interactions using peptide model systems, much less experimental data are available for globular proteins. We have attempted to determine the magnitude of cation-pi interactions of Lys with aromatic amino acids in four different proteins (LIVBP, MBP, RBP, and Trx). In each case, Lys was replaced with Gln and Met. In a separate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 43 publications
3
55
0
1
Order By: Relevance
“…1) and the apparent amount of stabilization energy derived from the proposed interaction (Fig. 2) would be in useful agreement with literature on geometrical and energetic features of the cation-p interaction [32][33][34][35]. However, interpretation of kinetic consequences resulting from site-directed substitutions of Phe 52 in terms of loss of local interaction energy must be made with caution.…”
Section: Free Energy Profiles For Reactions Of Wild-type and Mutated supporting
confidence: 86%
“…1) and the apparent amount of stabilization energy derived from the proposed interaction (Fig. 2) would be in useful agreement with literature on geometrical and energetic features of the cation-p interaction [32][33][34][35]. However, interpretation of kinetic consequences resulting from site-directed substitutions of Phe 52 in terms of loss of local interaction energy must be made with caution.…”
Section: Free Energy Profiles For Reactions Of Wild-type and Mutated supporting
confidence: 86%
“…A highly charged Arg-857 might push the equilibrium to the conformational state where the protein is stabilized in its inactive state via the cation-p interaction. Interestingly, it has been shown that elevated temperatures stabilize cation-p interactions (Prajapati et al, 2006). A temperature-dependent inactivation of BRI1 would be consistent with the temperaturesensitive dwarfism found in uzu1.a.…”
Section: Lodging-resistant Barley In a Changing Climatesupporting
confidence: 69%
“…Cation-p interactions are common in proteins, and their energetics seem to be highly dependent on the specific residue pair involved [28,29]. The crystallographic data suggest that, in addition to disrupting the Phe2-Arg25 interaction, Gly25 causes instability by dramatically changing the side chain volume [15].…”
Section: Discussionmentioning
confidence: 99%